Management Of Physiotherapy In Bronchial Asthma With Modality Infra-Red, Chest Therapy,And Respiratory Muscle Stretch Gymnastic - Maesaroh, Siti; Nahdhliyyah, Ade Irma (Pena Medika Jurnal Kesehatan, 2023)
Bronchial asthma is an obstruction of airflow characterized by an increase in airway sensitivity to the shape of external stimulation. Physiotherapy examination includes an examination of spasm, examination of sputum, examination of thoracic cage expansion, examination of shortness of breath, examination of pain, and examination of functional activity. In this case, the chosen technology is Infra Red(IR), Chest Therapy, and Respiratory Muscle Strech Gymnastic (RMSG). The research aim to determine the effect of physiotherapy management in cases of bronchial asthma. The study was conducted at the Surakarta Center for Lung Health Society with analytic descriptive methods. Subjects were bronchial asthma patients with modality IR, Chest Therapy ,and RMSG. The data collection method of research analysis is by auto anamnesis method, the research instruments are examination of spasm with palpation, sputum with auscultation, thoracic cage expansion with midline, shortness of breath with the Borg Scale, pain with a VAS scale and functional activity with a six-minute walk test. Results: After 3 times of therapy as follows: (1) no decrease in spasm T1 = 1 at T3 = 1 (2) Reduction of sputum T1 = 2 at T3 = 1 (3) Increase in thoracic cage expansion of T1 difference in axilla = 2, ICS 4-5 = 3, Proc. Xypoideus = 2 becomes T3 at axilla = 2.5, ICS 4-5 = 3, Proc. Xypoideus = 2 (4) Reduction in shortness of breath T1 = 3 at T3 = 0 (5) Reduction in pain T1 = 3 at T3 = 1 (6) Increase in functional activity T1 = 330 meters at T3 = 360 meters.Physiotherapy intervention withmodalityIR, Chest Therapy, and RMSG can reduce the problems that exist in the condition of Bronchial Asthma.